Methods of drawing up tasks for formative assessment through digital educational resources - Мусахан, Рыскүл; Боранкулова Дина Мэлсовна (Pedagogy and Psychology, 2022)
The article touched upon a number of issues aimed at identifying effective aspects of changes in the education system. Surveys were conducted to determine the ways of using new technologies in accordance with the requirements of modern society, problems were identified, solutions were analyzed, conclusions were given. Currently, during the formation of the informatization system, education issues are being resolved in a timely manner, new methods, projects, and methodological recommendations are being developed. Their effectiveness or inefficiency lies in the quality of formative assessment tasks that teachers make up in accordance with the approved goals of the daily lesson plan. To educate a person, an approach is needed that increases the interest of students in the formation of independent thinking skills, commenting on conclusions, identifying problems and making decisions. The proposed article served as a guide for teachers in creating tasks that increase interest, training with the help of information tools quizizz.com valuable information about the online service and screenshots of images from personal experience are presented. Examples of formative assessment tasks that can be included in the lesson plan in connection with the section "Hydrosphere" are given. However, the daily use of this service can quickly cause boredom in students, so when using online services for drawing up a lesson plan, on complex topics for educational purposes, expanding the space of the didactic fund, we can fully achieve the learning goals.